Introduction - María José Alcaraz León (Estetika, 2023)
Recent debates on the validity of Aesthetic Testimony and the centrality of the so-called Acquaintance Principle suggest that there is more to the proper exercise of aesthetic judgement than mere endorsement of allegedly correct aesthetic judgements. For example, although it is reasonable to follow experts’ judgements in certain matters of fact, it seems less acceptable to simply endorse or adopt experts’ judgements in the aesthetic domain. That reliance on testimony, by contrast to some other areas of judgement, is not sufficient for aesthetic judgement has encouraged scholars to focus in turn on the importance of the personal involvement and autonomy of the aesthetic agent. This special issue focuses on phenomena related to failed exercises of aesthetic judgement. The choice of the theme is motivated by the belief that a careful analysis of failures in aesthetic judgement can reveal significant aspects of the nature of aesthetic experience itself as well as the roles that perception, imagination, and learning have in its proper exercise.